Keunggulan Bersaing UMKM Industri Pangan di Bandar Lampung - Evi Yuniarti; Fitriani Fitriani; Dwi Puji Hartono; Nurmala Nurmala (Politeknik Negeri Lampung, 2021)
MSMEs sector is so important because this sector has a share of up to 60% in Gross Domestic Product (GDP). But the Central Statistics Agency (BPA) conducted a survey in August and found that the incomes of cooperatives and MSMEs decreased during the pandemic. The current study was conducted to re-examine the effect of innovation, digital marketing, and accounting application on competitiveness enhancement of MSMEs in the food industry sector. Data were collected through structured questionnaires using a sample size of 100 food industrial MSMEs operating in the emerging market of Bandar Lampung. Hypotheses were tested through multiple regression models using SPSS 22. The results indicate that Innovation has a significant impact on competitive enhancement and MSMEs performance. Digital Marketing has a significant impact on competitive enhancement and MSMEs performance. Lasting the accounting application has a significant impact on competitive enhancement and MSMEs performance. Firms are required to create an effective business model to acquire competitive advantage and superior financial performance. Implications for practice have been discussed.